Iron Deficiency in Depressive Disorders: A Review of Mechanisms, Clinical Relevance, and Treatment Perspectives - Wycik, Michał; Kondratiuk, Gabriela; Kruk, Agnieszka; Łupińska, Marta; Stępień, Kamila; Kucińska, Julia; Chmielewski, Hubert; Wądołowski, Artur; Przeniosło, Joanna; Komar, Julia (Quality in Sport, 2025)
Purpose of the research: Iron deficiency (ID) is one of the most common nutritional deficiencies globally and may play a role in the development of depressive symptoms, even in the absence of anemia. This review explores the physiological links between iron status and brain function, examines current evidence on the association between iron deficiency and depression, and evaluates the impact of iron supplementation as a potential adjunctive treatment in depressive disorders. Materials and methods: A narrative review was conducted using articles identified from PubMed and Google Scholar. Studies included observational data, clinical trials, and systematic reviews. The analysis focused on populations with iron deficiency (with or without anemia) and assessed the effects of iron status and supplementation on mood and psychiatric symptoms. Results: Iron plays a crucial role in monoamine neurotransmitter synthesis, energy metabolism, and brain development. Several studies suggest that ID may contribute to depressive symptoms, including fatigue, apathy, and low mood. Supplementation with iron, both oral and intravenous, has shown potential in improving mood, reducing fatigue, and enhancing response to antidepressant therapy, particularly in populations with iron deficiency without anemia. Conclusions: Iron deficiency may be an underrecognized factor in the development and persistence of depression. Routine assessment of iron status and appropriate supplementation could serve as a valuable adjunct in the management of depressive disorders. Further research is needed to establish standardized diagnostic criteria and treatment protocols.